Maturity Modeling of the Nakhon Basin, Gulf of Thailand - Prueksuwat, Athittan (Bulletin of Earth Sciences of Thailand, 2021)
The maturity of Oligocene potential source rocks in the Nakhon Basin was evaluated with a 1D maturity model that was calibrated with vitrinite reflectance data. Burial and thermal histories during basin development were modeled assuming a subduction rollback tectonic and paleo-heat flow was calculated with a transient model. The maturity model suggests that most potential source rocks are currently in the early oil window; although approximately 40% of those in the northern sub-basin have reached the main oil window, as have approximately 10% of the source rocks in the southern sub-basin. These results suggest that there may not have been a significant amount of oil generated in the Nakhon Basin.